The Kaliningrad region as a strategic exclave of the Russian Federation and its implications on the security issues of the Baltic states and Poland - Alaverdian, Karina; Huntley, Matthew David; Kočí, Kateřina; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This thesis examines the Kaliningrad region as a strategic exclave of the Russian Federation and its implications on the security issues faced by the Baltic states and Poland in the light of securitization theory. The study critically analyzes the discursive practices employed by various actors to construct the region as a security concern. It also adds a comparison with an additional, third-party actor, and their interpretation of the region.
Vedoucí práce: Matthew David Huntley
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní studia - diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses